Transnational trajectories in East Asia (Abingdon, Oxon ; New York, NY)
xvii, 274 sayfa
Keywords: “In the last decades, regional and global interconnectedness in East Asia - through trade, investment, migration, and popular culture - has grown, while simultaneously we observe renewed national assertiveness and nationalist impulses in the region. The book interrogates these seemingly contradictory developments as they bear on the transformations of the nation and citizenship in East Asia. Conventionally, studies on East Asia juxtapose these developments, focusing on the much-exercised dichotomy of the national and transnational. In contrast, this book suggests a different orientation. First, it moves beyond the simplistic view that demarcates the transnational as “the West“. Second, it does not view the national and transnational as contradictory spheres of influence and analysis, but rather, focuses on the interactions between the two, with a view on how these interactions work to transform the ideals and practices of the “good nation“, “good society“, and “good citizen“. The chapters cover a broad range of case studies which highlight how the nation is contested in relation to transnational dynamics and frameworks, and the ways in which the relationship between the citizen and (national) collective is redefined, including education, science, immigration and multicultural policy, human rights, gender and youth orientations, contemporary art, cultural diplomacy and regional politics. Transnational Trajectories in East Asia will be of great interest to students and scholars of Asian studies, Asian politics, Asian culture and society, transnationalism, migration, citizenship and political sociology.“ --